Investigation on crack propagation in band-like rust layers on weathering steel. (26th April 2021) - Zhou, Lujun; Yang, Shanwu
Highlights: Rust layers on weathering steel consist of band-like structure. Cracks in rust layers propagate along a path parallel to interfaces of the bands. Crack propagation is driven by internal stress of rust rather than applied forces. Abstract: Crack propagation in rust layers on weathering steel was investigated in this paper. The applied stress by thermal shock will result in propagation of original cracks in the rust layers, along a path approximately parallel to the interface of rust layers/steel matrix, rather than nucleation of new cracks. The inner rust layers on weathering steel show higher thermal shock resistance than outer rust layers. The results can be attributed to that rust layers on weathering steel consist of light-shade alternating bands structure parallel to the interface, caused by alternation of in-depth development and transverse extension of corrosion.